Infarcted thymus presenting as cancer - Maria E. Tecos; Matthew Ballweg; Angela Hanna; Patrick Thomas; Abdalla Zarroug (Elsevier, 2022)
Thymomas are exceedingly rare in the pediatric population, with lymphoma being a much more likely etiology of a mediastinal mass in a child. Here, we present the interesting case of a large mediastinal mass incidentally identified in an 11-year-old female, which was initially concerning for malignancy. After extensive workup revealing the likely benign nature off the lesion, resection was pursued to relieve cardiopulmonary mass effect. Final pathology was returned as benign infarcted thymoma.